Effects of vaccination against COVID-19 on overactive bladder symptoms on young population - de-la-Plaza-San-Frutos, Marta; García-García, Elisa; Martínez-Pascual, Beatriz; Esteban, Isabel Mínguez; Domínguez-Balmaseda, Diego; Sosa-Reina, M. Dolores (Frontiers in Medicine, 2024)
Introduction The vaccines developed against COVID-19 have different modes of action, with a primary focus on the spike protein of the virus. Adverse effects following vaccination have been reported, including local and systemic symptoms. Understanding the potential side effects on the urinary tract after vaccination is of importance. Actively investigating and comprehending the potential impact on the urinary tract, we can enhance public health strategies and pave the way for safer and more effective vaccination programs. Methodology The study was based on an online survey that included the Spanish Version of the Overactive Bladder Symptom Score (OABSS-S); 2362 men and women replied to the survey. After the application of the exclusion criteria, 1563 participants were insured. In the context of COVID-19, individuals were questioned regarding several key factors related to their vaccination status and medical history. These factors included the number of vaccine doses received, the specific type of vaccine administered, whether they had previously contracted COVID-19, and the frequency of prior infections, if applicable. Results A total of 1563 (74,7% women and 27,3% men) subjects between the ages of 18 and 45 completed the survey and were included in the final analyses. The most frequently administered vaccine type was Pfizer-BioNTech (42.2%), and most subjects received three doses. The proportion of females who received the AstraZeneca vaccine and do not require to urinate during the night is significantly higher compared to males (59.1% vs. 33.3%; p<0.05). The proportion of individuals who urinate five or more times during the night is higher in those who have received a single vaccine dose than in those who have received three doses (2.2% vs. 0.1%; p<0.05). Conclusion COVID-19 vaccination has been found to impact the lower urinary tract (LUT) and overactive bladder (OAB). Initially, LUT symptoms worsened, and OABSS-S scores increased after the first vaccine dose in individuals under 45 years old. However, symptoms improved after receiving the third and fourth doses. Gender differences were observed in the vaccination effects. Men vaccinated with AstraZeneca reported a higher number of nighttime voids, while women vaccinated with Moderna reported more daytime voids.